Opto-CD28-REACT: optogenetic co-stimulatory receptor activation on non-engineered human T cells - Ehret, Anna K.; Hartmann, Sara; Salavei, Pavel; Andreani, Virginia; Gensch, Nicole; Gámez-Díaz, Laura; Schamel, Wolfgang W. (Frontiers in Immunology, 2025)
T-cell activation is a highly regulated process requiring both antigen recognition via the T-cell receptor (TCR) and co-stimulatory signaling, notably through the co-stimulatory receptor CD28. Here, we introduce an optogenetic platform for reversible and tunable full activation of human T cells that does not require genetic modification. We engineered opto-CD28-REACT, a recombinant protein comprising an anti-CD28 single-chain variable fragment, GFP, and phytochrome-interacting factor 6 (PIF6). This construct binds CD28 and thereby attaches PIF6 to CD28. Upon red light (630 nm) illumination, PIF6 binds to PhyB tetramer-coated beads, triggering CD28 signaling that can be attenuated by far-red light (780 nm) in 2 min. We show that opto-CD28-REACT synergizes with opto-CD3ϵ-REACT—a complementary optogenetic tool targeting the TCR complex—to induce light-dependent activation of both Jurkat cells and primary human T cells. Co-stimulation through both opto-REACT systems promotes ERK phosphorylation, upregulation of the activation markers CD69 and CD25, interleukin-2 (IL-2) secretion, and T-cell proliferation, reaching levels similar to conventional antibody-mediated stimulation. This strategy enables precise optical control over TCR and CD28 signaling in non-genetically modified T cells, offering a powerful approach for dissecting the regulatory dynamics of T-cell activation and advancing applications in synthetic immunology.